A OQAM (Offset QAM) based Filter bank Multicarrier Modulation (International Journal of Communication Systems and Network Technologies, 2019)
Filter bank Multicarrier Modulation techniques are new generation evolution and they are dominating the currently adopted Orthogonal Frequency Division Multiplex (OFDM) being used for the latest commercial mobile communication applications. FBMC i.e filter bank multicarrier modulations are implemented with the help of filter analysis and synthesis filter banks obeying the Nyquist criteria for pulse shaping. The offset quadrature modulation is advantageous in achieving better baud-rate by using in-phase and quadrature components of QAM symbols and recovering the information symbols with minimized intersymbol interference (ISI) and intercarrier interference (ICI).Better spectral efficiency and low out of band radiation is achieved as compared to OFDM modulation. In this paper we first analyse the offset quadrature maodulation based FBMC model explore the Nyquist criteria used for pulse shaping and implementation of the polyphase structures of FBMC transmitter and receiver are discussed with various field applications of FBMC.
Keywords: Multicarrier Systems; FBMC; Nyquist-Filters; OFDM OQAM; Polyphase Structures